Foreign exchange reserve accumulation in the ASEAN-4 challenges, opportunities, and policy options - Park, Donghyun; Estrada, Gemma Esther B. (The Philippine Review of Economics, 2010)
The ASEAN-4 countries-Indonesia, Malaysia, Philippines, and Thailand-have large and growing stocks of foreign exchange reserves. The region's reserves now comfortably exceed levels required for traditional liquidity purposes. This has led to calls for a more active management of reserves, which would yield higher risk-adjusted returns. This paper examined the various opportunities and challenges associated with more active, profit-oriented management of reserves in the ASEAN-4.